Atomistic Understanding of the Ferroelectric Properties of a Wurtzite‐Structure (AlN)n/(ScN)m Superlattice. Issue 5 (17th May 2021) - Ye, Kun Hee; Han, Gyuseung; Yeu, In Won; Hwang, Cheol Seong; Choi, Jung-Hae
Abstract : In article number 2100009, the ab initio calculations by Cheol Seong Hwang, Jung‐Hae Choi, and co‐workers show that wurtzite‐type AlN can have a suitable range of ferroelectric switching barrier ( E a) and spontaneous polarization ( P s) by forming superlattice structures with ScN. The E a is dominated by the local structure instability, while the P s is significantly affected by the structural parameters and the Born effective charge.